Molluscicidal and cercaricidal activities of curcumin on Biomphalaria glabrata and Schistosoma mansoni cercariae. Issue 4 (8th November 2019) - Matos, Jaqueline L; da Silva, Karen R; de Lima Paula, Lucas A; Cunha, Wilson R; Ramos, Salvador B; Rodrigues, Vanderlei; Cabral, Fernanda J; Magalhães, Lizandra G
Abstract: BACKGROUND: Schistosomiasis control in endemic areas depends on several factors, including chemotherapy, snail control and adequate sanitation. In this context, the employment of compounds isolated from plants is an important issue regarding infection and snail control. The aim of this study was therefore to evaluate the effects of curcumin (CUR), a compound isolated from Curcuma longa, against snails and embryos of Biomphalaria glabrata, which is the most important intermediate host of schistosomiasis in the Americas, as well as in cercariae, the infecting larval stage of Schistosoma mansoni . RESULTS: CUR presented high activity against B. glabrata embryos and moderate activity against newborn and adult snails. The lethal concentration (LC50 ) values after being exposed for 24 h and evaluated for 7 days were 6.54 (95% confidence interval (CI) 5.86–7.30) μg mL −1 for the embryos and 42.29 (95% CI 33.82–52.87) μg mL −1 and 87.69 (95% CI 68.82–111.7) μg mL −1 for the newborn and adult snails, respectively. Moreover, CUR inhibited the development of embryos and egg hatching, and decreased the fecundity rates of adult snails. CUR also demonstrated cercaricidal activity with LC50 values lower than 10 μg mL −1 at 1, 3, 6, 9 and 12 h, respectively. CONCLUSION: Our data show that CUR has potential molluscicidal and cercaricidal activities. Moreover, as a nutraceutical compound that is toxic to both invertebrate host and parasite, CUR has the potential to be explored as a safe new agent to combat schistosomiasis. © 2019 Society of Chemical Industry Abstract : This article indicates that curcumin (CUR) is effective against B. glabrata embryos and the cercariae of S. mansoni, and highlights the potential of natural compounds in the chemoprophylaxis of schistosomiasis.